Qana’ah Dalam Al-Qur’an (Studi Komparatif Tafsir Al Azhar Dan Tafsir Al Mishbah) - Nurul Amalia Azlikah; Fathoni (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to examine the concept of qana’ah in the Qur’an through a comparative study between Tafsir Mishbah by Quraish Shihab and Tafsir Al Azhar by Buya Hamka. The main issue raised in this study is the understanding of qana’ah, which is the attitude of feeling sufficient with what Allah has given. The theory used to analyze this concept is the view of two great Indonesian scholars, namely Buya Hamka and Quraish Shihab.  The results of the study show that these two interpretations have similarities in their explanation, namely qana'ah means having the nature of sufficient with what has been given by Allah, without feeling less or excessive. This study makes an important contribution in understanding how qana’ah is perceived and applied in everyday life in accordance with the guidance of the Qur’an, as explained by the two scholars.